1996
DOI: 10.1063/1.362922
|View full text |Cite
|
Sign up to set email alerts
|

High-field fast-risetime pulse failures in 4H- and 6H-SiC pn junction diodes

Abstract: We report the observation of anomalous reverse breakdown behavior in moderately doped (2-3x 1017 cm -3) small-area micropipe-free 4H-and 6H-SiC pn junction diodes. When measured with a curve tracer, the diodes consistently exhibited very low reverse leakage currents and sharp repeatable breakdown knees in the range of 140-150 V. However, when subjected to single-shot reverse bias pulses (200 ns pulsewidth, 1 ns risetime), the diodes failed catastrophically at pulse voltages of less than 100 V. We propose a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Both increasing and decreasing breakdown voltage with increasing temperature has been reported for 4H. [6][7][8] In the present letter we investigate the temperature dependence of avalanche breakdown in chemical vapor deposition ͑CVD͒-grown p-n diodes in 4H silicon carbide, both for uniform and microplasma breakdown. A study of 6H devices has also been performed for the purpose of comparison.…”
mentioning
confidence: 95%
“…Both increasing and decreasing breakdown voltage with increasing temperature has been reported for 4H. [6][7][8] In the present letter we investigate the temperature dependence of avalanche breakdown in chemical vapor deposition ͑CVD͒-grown p-n diodes in 4H silicon carbide, both for uniform and microplasma breakdown. A study of 6H devices has also been performed for the purpose of comparison.…”
mentioning
confidence: 95%
“…The SiC samples were grown in an intermediate frequency (2,500 Hz) inductively heated furnace by using PVT method. In a series of crystal growth runs, 2-in 6H-SiC crystals and 2-in 4H-SiC crystals were grown on Si-terminated 6H seeds and C-terminated 4H seeds, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Silicon carbide (SiC) is a very promising semiconductor material for electronic applications because of its excellent electronic properties, super thermal and chemical stabilities, and high-power and high-frequency capabilities, as well as very good tolerance to radiation damage [1][2][3][4]. On top of these, SiC single crystal is attractive for being the substrate in the heteroepitaxial growth of other important materials [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…All these properties often make traditional semiconductor and junction models inapplicable in the case of SiC. First experimental evidence of the doping carrier freeze-out influence on SiC device performance has been demonstrated by Neudeck et al, 4 who observed a reduction of the statically measured pn junction breakdown voltage when fast-risetime pulse was applied to the junction. Lades et al 5 simulated the influence of incomplete doping ionization on transient behavior of SiC pn diode, MOSFET and thyristor.…”
Section: Introductionmentioning
confidence: 98%